Mikey Reynolds: capstone - Reynolds, Mikey, artist (Colorado State University. Libraries, 2025)
The artist's statement: I would like to live a life in clay. I wonder why clay remains so rare in our world. What can't clay do? It seems nearly limitless if one is to just put in the effort to understand where there is friction. This is where the process, the how, becomes so important. It is one thing to have an idea of what clay could be or what could be made with clay, but it is another entirely to figure out the way to do it. Clay is about doing, and I love the doing. My style involves a reciprocal relationship with clay. I do not always know what I am making while I am working. I trust that when I push clay, the clay will push me. The pottery wheel is a favorite tool because of its unlimited potential to create radially symmetrical building blocks (or modules). Once something is off the wheel, it can be transformed, altered and combined with other parts. When designing, I account for the mass of each part and how that builds into a sturdy, stout whole with its own (gravitational) pull. Further, I look at lines traced out by the edge of three-dimensional forms paying careful attention to how they interact to build concentricity and continuity. I move around and try to align edges differently. I realize that the work is placing me in space just as much as I choose where to place the work. Using slips, underglazes and glazes I have prepared, I build layers of pattern. Each mark can be traced to a repeated action. Every repetition is a variation on a theme and a search for an authentic action and the mark it leaves. Can process be honest? This question regarding material and gestural reality fascinates me, and I believe clay may have the answer. A ceramic object is full of clues. Playing detective with a mug or bowl can be very stimulating because we can feel how something is made. Pots are beautiful because they are bold, and they are honest. They reveal all the modules of their character to the world. Many external influences shape what I do and how I do it. From the hidden images in drywall and clouds, the patterns and lessons offered by plants, the potential in a brush soaked in slip, to candy and the sweet pleasure of just filling space, I draw in inspiration at every breath. I bring these moments to the clay, and in its memory it records them. The rarity, yet paradoxical inevitability, of life holds me in a place of curiosity. I bring my questions to the clay, and it offers me the chance to find answers. Better yet, it leaves me with a bounty of more-refined questions. I wonder what I will get to do next.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery